STABILITY PARAMETERS OF MUNG STRAINS IN SOUTHERN PUNJAB - Akhtar, Lal Hussain; Arshad, Muhammad (Biological Sciences - PJSIR, 2004)
Three genotypes of mung (Vigna radiata) i.e. BRM-188, BRM-195 and BRM-202 along with two check varieties (NM-92 and NM-98) were evaluated at five different locations (i.e. Bahawalpur, Multan, Vehari, Khanewal and Dera Ghazi Khan) in Southern Punjab for two consecutive years (2001 and 2002). The genotype BRM-195 was found to be the most stable genotype across a variety of location/environment with regression coefficient (bi) of 1.062 and disper- sion (Sd2) of 0.052 followed by BRM-188 and BRM-202. The genotype BRM-195 performed better across all the locations (3056 Kg ha-1) by producing 46.2 and 60% higher yield than the check varieties i.e. NM-92 and NM-98, respectively. The genotype BRM-195 was being evaluated as a candidate variety in National Uniform Mung Yield Trials by the Coordinator Pulses, National Agricultural Research Centre, Islamabad, for its release for general cultiva- tion in the Southern Punjab.